Learner Autonomy Desirability and Feasibility in Indonesian EFL Classrooms: University Students’ Voices - Slamet Wahyudi Yulianto (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2019)
For its promises in helping learners to develop their language proficiency, independent learning skill, thinking skill, and collaborative skill, numerous research and practices have been conducted regarding the promotion of Learning Autonomy (LA) in English as a Foreign Language (EFL) classroom. However, the majority of research focuses only on the teachers’ viewpoint. This paper aims to reveal the students’ voices towards LA, especially its’ desirability and feasibility in the context of EFL classroom in Indonesia. This case study was carried out in one private university in Subang. 44 students were purposively selected as the participants. The data were collected through distributing questionnaires and conducting interviews. It is revealed that most of participants perceive LA as both desirable and feasible. However, they still find that it is not easy to develop their LA without adequate support from their teachers. It can be concluded that the students are willing to develop their LA. It is suggested that there should be more teacher training regarding the promotion of LA in the Indonesian EFL context.